Corrosion Behavior of Dental Alloys Under Artificial Saliva Solution with Different pH Values - Chang, Yen-Hao; Pan, Yan-Ting; Chao, Chih-Yeh; Lee, Huey-Er; Wu, Ju-Hui (The Journal of Dentists, 2022)
The purpose of this study was to investigate the corrosion behavior of four different dental casting alloys in artificial saliva solutions with varying pH values. Microstructures were observed using scanning electron microscopy. The corrosion behavior of the experimental alloys in artificial saliva was examined using potentiodynamic polarization measurements. The high noble alloy (Au-8.5Pt-2.6Pd-1.4In) exhibited better corrosion resistance with lower anodic current densities in the pH range of 3–5. The anodic current density of the noble alloy (Au-24.9Pd-19.0Ag-5.5In) decreased as the pH decreased. The noble (Pd-37.7Ag-8.5Sn) and base metal (Ni-25Cr-11.5Mo-1.4Si) alloys exhibited lower corrosion resistance with a relatively high current density at pH 3. Compared with noble alloys, base metal alloys exhibited good corrosion resistance in this study. This makes them a promising material for dental castings considering the complex pH changes in the oral environment.